2009
DOI: 10.3928/01484834-20091113-11
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Quality and Safety Competency Development at the Unit Level: An Initial Evaluation of Student Learning and Clinical Teaching on Dedicated Education Units

Abstract: The need to attend to quality and safety competency development, increase capacity in nursing education programs, address the faculty and nursing shortages, and find new ways to keep step with an ever-changing health care environment has brought forth numerous creative curricular responses and collaborative efforts. To tackle these multiple needs and challenges simultaneously, a new academic-service partnership was created to collaboratively develop an innovative clinical education delivery model. The designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…DEUs are ). There were greater opportunities for "teachable moments" due to students' increased "time-on-task" practicing nurses (Mulready-Shick et al, 2009). Other researchers have found that students were well supported during clinical placements because all staff participated in student teaching and that the use of DEUs in nursing curriculum eased NLRN transition to practice and improved satisfaction (Casey et al, 2008;Walker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DEUs are ). There were greater opportunities for "teachable moments" due to students' increased "time-on-task" practicing nurses (Mulready-Shick et al, 2009). Other researchers have found that students were well supported during clinical placements because all staff participated in student teaching and that the use of DEUs in nursing curriculum eased NLRN transition to practice and improved satisfaction (Casey et al, 2008;Walker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,8,11,12] The authors of this article also recognized advantages to this model, including the ability to increase enrollment without additional faculty. The limitations of this project include a small number of participants and restricted evaluation timeframe, which make it difficult to draw conclusions or make comparisons to other methods of clinical instruction.…”
Section: Resultsmentioning
confidence: 99%
“…[10] The effectiveness of a DEU model in developing a "community of practice" was confirmed in 2009. [11] Interviews with 34 DEU participants found that one reason for success of the DEU was key relationships within the DEU. The specific themes threaded through the interviews included (a) engaging in recurring communication to achieve shared objectives, (b) problem solving to maintain valued relationships, (c) working together toward mutual outcomes, (d) recognizing unfamiliarity in changing roles and responsibilities, (e) valuing interdependence, complementary competence, and equalizing power balance, (f) witnessing the effect of teamwork upon positive change and quality improvement, and (g) advocating for a DEU future amidst low certainty and little agreement on next steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55,61,62] Students have reported that it is easier to learn about potential adverse event alerts with a smaller student-to-teacher ratio. [63] It is, therefore, critical that nursing students should receive optimal supervision in order to become safe, competent and independent health care practitioners. The impact of supervision must become an urgent research and practice priority for undergraduate nursing education programs.…”
Section: Discussionmentioning
confidence: 99%